2015
DOI: 10.1186/s13063-015-1098-y
|View full text |Cite
|
Sign up to set email alerts
|

Oral versus intravenous antibiotic treatment for bone and joint infections (OVIVA): study protocol for a randomised controlled trial

Abstract: BackgroundBone and joint infection in adults arises most commonly as a complication of joint replacement surgery, fracture fixation and diabetic foot infection. The associated morbidity can be devastating to patients and costs the National Health Service an estimated £20,000 to £40,000 per patient.Current standard of care in most UK centres includes a prolonged course (4–6 weeks) of intravenous antibiotics supported, if available, by an outpatient parenteral antibiotic therapy service. Intravenous therapy carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…Bone and joint infections, particularly when the implant is not removed, require at least 6 to 12 weeks of antibiotic treatment according to the majority of current guidelines. A recent unblinded and randomized trial (OVIVA) confirmed that oral antibiotic treatment is as effective as intravenous administration in bone, joint, or metalware-associated infections (17). The better results with oral antibiotics have been demonstrated with levofloxacin plus rifampin; however, other oral alternatives combined with rifampin have been associated with lower remission rates (8,11), in part due to a worse safety profile but also to a reduction in the serum concentration of companion drugs like clindamycin, co-trimoxazole, linezolid, or fusidic acid (18)(19)(20)(21), in contrast to what has been shown with fluoroquinolones (10).…”
Section: Discussionmentioning
confidence: 99%
“…Bone and joint infections, particularly when the implant is not removed, require at least 6 to 12 weeks of antibiotic treatment according to the majority of current guidelines. A recent unblinded and randomized trial (OVIVA) confirmed that oral antibiotic treatment is as effective as intravenous administration in bone, joint, or metalware-associated infections (17). The better results with oral antibiotics have been demonstrated with levofloxacin plus rifampin; however, other oral alternatives combined with rifampin have been associated with lower remission rates (8,11), in part due to a worse safety profile but also to a reduction in the serum concentration of companion drugs like clindamycin, co-trimoxazole, linezolid, or fusidic acid (18)(19)(20)(21), in contrast to what has been shown with fluoroquinolones (10).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary outcomes included possible and probable treatment failure, serious adverse events, IV catheter complications, Clostridium difficile infections, early termination of randomized therapy, and resource utilization. The full methodological details are available in the published protocol (60).…”
Section: Versus Oral Antibiotics For Osteomyelitis: Lessons From Tmentioning
confidence: 99%
“…Studies are underway to assess whether the strategy of using oral therapy (usually utilising oral bio‐available agents with appropriate spectrum of activity and good bone penetration) is non‐inferior to traditional IV therapy in bone and joint infection (including diabetes‐associated osteomyelitis) . A published Cochrane review of a small number of appropriate studies has suggested equipoise, except in patients with septicaemia.…”
Section: Antibiotic Therapy: Risks Benefits and Complicationsmentioning
confidence: 99%